Thoracic Endovascular Aortic Repair With Single/Double Chimney Technique for Aortic Arch Pathologies. (June 2017) - Wang, Tun; Shu, Chang; Li, Ming; Li, Quan-ming; Li, Xin; Qiu, Jian; Fang, Kun; Dardik, Alan; Yang, Chen-zi
Purpose: To summarize a single-center experience using the single/double chimney technique in association with thoracic endovascular aortic repairs (TEVAR) for aortic arch pathologies.Methods: From November 2007 to March 2016, 122 patients (mean age 50.4±12.7 years, range 29–80; 92 men) with aortic arch pathologies underwent TEVAR combined with single (n=101) or double (n=21) chimney grafts to reconstruct the supra-aortic branches: 21 innominate arteries, 114 left common carotid arteries, and 8 left subclavian arteries (LSA). Pathologies included type B aortic dissection (n=47), aortic arch dissection (n=49), retrograde type A aortic dissection (n=8), thoracic aortic aneurysm (n=7), penetrating aortic arch ulcer (n=9), and post-TEVAR type I endoleak (n=2). Follow-up examinations included computed tomography at 0.5, 3, 6, and 12 months and yearly thereafter.Results: The aortic stent-grafts were deployed in zone 0 (n=21), zone 1 (n=93), and zone 2 (n=8). One (0.8%) of the 122 patients died at 4 days due to a perforated peptic ulcer. Type Ia endoleaks were found intraoperatively in 13 (10.7%) patients, including 3 with the double chimney technique. Type II endoleaks occurred in 6 (4.9%) patients; 3 were treated with duct occluders in the LSA. Postoperative chimney graft migration occurred in 1 (0.8%) patient with double chimneys; additional stent-grafts were deployed in both chimneys. Median follow-up was 32.3 months, during which 1 (0.8%) patient died after a stroke at 3 months. Chimney stent-graft patency was observed in the remaining 120 patients. Two (1.7%) secondary TEVARs were performed for distal aortic dissection. Nine asymptomatic type Ia endoleaks and 1 type II endoleak persisted in follow-up; a type II endoleak in 1 patient with Marfan syndrome sealed in 52 months.Conclusion: TEVAR with the chimney technique provides a safe, minimally invasive alternative with good chimney graft patency and low postoperative mortality during midterm follow-up. The double chimney technique should be used judiciously owing to its potential complications.